Library patrons' emotions after information retrieval: effects of perceived self-efficacy. Issue 3 (4th July 2016) - Mohd Suki, Norazah; Mohd Suki, Norbayah
Abstract : Purpose: – Successful information retrieval is determined by library patrons retrieving accurate, relevant, and up-to-date information stored in documents; this affects their self-efficacy, emotions, and behavior. The purpose of this paper is to examine the impact of mastery experiences, self-evaluation, vicarious observation of others' experiences, social feedback, and physiological state of library patrons' emotions after information retrieval. Design/methodology/approach: – A structured close-ended questionnaire survey was utilized of which 200 responses were valid and usable for data analysis. Multiple regression analysis was executed to assess the influence of personal self-evaluation, comparisons with others, physiological state, and social feedback, on the library patrons' emotions after information retrieval. Findings: – The findings of this study indicated that social feedback had the greatest influence on the library patrons' emotions after information retrieval, followed by personal self-evaluation and physiological state. Originality/value: – This study employed quantitative research design utilizing multiple regression analysis which provides useful insight for university librarians on the specific factors that have significant effects on library patrons' emotions after information retrieval. The outcomes add a new perspective to preceding studies on library patrons' emotions after information retrieval, which has previously been inadequately researched in the Malaysian setting.